Research and policy for the food-delivery revolution: Implications for nutrition, environment, and work may be considerable - Meemken, Eva-Marie; Bellemare, Marc F.; Reardon, Thomas; Vargas, Carolina M. (American Association for the Advancement of Science, 2022)
Implications for nutrition, environment, and work may be considerable